Lagorio’s Wall in the Crimea: pages of scientific activity of the geologist Oleksandr Lagorio - Dmytro Mikhalenok (Geo&Bio)
The paper presents selected pages from the biography and scientific activity of the world-famous geologist Oleksandr Lagorio (1852–1944). The formation of the Lagorio’s scientific views in the universities of Dörpt (now Tartu, Estonia) and Warsaw (now Poland) are shown. In the latter, a wide profiled scientific school of the scientist was formed, including synthetic geology (experimental mineralogy and petrography)—the most well-known representative of which was the Polish scientist Józef Morozewicz, crystallography (Georg Wulff), and applied and theoretical geology (Dmitro M. Sobolev). First published is the letter to V. I. Vernadsky (dated to 30 December 1893) with a request to provide care for his students. The information presented provides further details to the biography of all those mentioned in the letter. Lagorio studied the processes of magma differentiation—Lagrio’s rule is now well-known in petrography. His research laid foundation for the physicochemical direction in petrography. In the Crimea, in various years between 1877 and 1897, the scientist studied the outcrops of igneous rocks considering their active influence on the formation of the relief. His theoretical views on the relations between igneous rocks and tectonics remain relevant until these days. All outcrops of igneous rocks were attributed to one magmatic centre, and the scientist estimated their age as Upper Jurassic–Lower Cretaceous. In the Crimea, the scientist first discovered granites, schists, the rock taurit, the mineral natrolite, etc. Details of the scientist’s excursion to Kara-Dag (published in French), which took place in September 1897, with participants of the VII International Geological Congress are presented: it was the first presentation of geological objects as an open-air museum to the scientific community. During the excursion, the scientist drew particular attention to a picturesque, large and majestic dyke. In the scientific literature and toponymy of the early 20th century, the dyke was called Lagorio’s Wall as a tribute to the outstanding geologist, native and researcher of the Crimea, whose scientific ideas continue to fascinate researchers. Details of an excursion to the Crimean Mountains also led by Oleksandr Lagorio are briefly described. The two excursions laid the foundation of international scientific tourism to the Crimea. The scientist’s views on the age of igneous rocks were confirmed by other domestic researchers and have been further developed in geological science.